2021
DOI: 10.1177/17411432211019417
|View full text |Cite
|
Sign up to set email alerts
|

A phenomenological inquiry into the influence of crucible experiences on the leadership development of Black women in higher education senior leadership

Abstract: Supported by the Crucibles of Leadership theory, this article explores how adverse experiences influence the leadership development of Black women in higher education senior leadership. I use phenomenology to explore how these leaders’ adverse lived experiences manifested as transformative crucible experiences with resilience, thus promoting leadership development. Black people have been continuously subject to adversity, while Black women have overcome the compounded adversities resulting from their intersect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…With the occurrences of COVID-19 disparities, lingering economic equities, and social unrest, continued insight is needed into Black women’s experiences as faculty and leaders in higher education [ 47 ]. Black faculty and other faculty of color have been continually underrepresented in higher education [ 13 ].…”
Section: Black Women In Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…With the occurrences of COVID-19 disparities, lingering economic equities, and social unrest, continued insight is needed into Black women’s experiences as faculty and leaders in higher education [ 47 ]. Black faculty and other faculty of color have been continually underrepresented in higher education [ 13 ].…”
Section: Black Women In Higher Educationmentioning
confidence: 99%
“…This intersecting level of racial and gender discrimination persists at every level of academic life, leading to faculty and students viewing Black women scholars as less capable and resulting in fewer full-time, tenured positions for Black women faculty [ 52 ]. Addressing these issues is further complicated as Black women seldom hold administrative positions in universities [ 52 ] and are underrepresented in higher education leadership [ 47 ]. The history of Black women in U.S. higher education can be described as a lesson in persistence, courage, and overcoming diversity, complete with persistent challenges, such as the gender pay gap, the concrete ceiling, regulated availability, power struggles, limited role models, privilege, tokenism, invisibility, microaggressions, and isolation [ 57 , 58 ].…”
Section: Black Women In Higher Educationmentioning
confidence: 99%
“…After data analysis, Chance (2021) identified three themes: 1) adversity, 2) education, and 3) leadership. Chance (2021) found that all participants had experienced significant adversity at different points in their lives, starting in childhood. Some of the severe adverse experiences included verbal, sexual, and physical assault and abuse, life-threatening illnesses, and unforeseen deaths of people close to them.…”
Section: The Intersection Of Trauma Gender Ethnicity and Leadershipmentioning
confidence: 99%
“…Furthermore, researchers have yet to explore this topic exclusively among Latina leaders at postsecondary institutions (Arnold et al, 2018;Breisch & Lexmond, 2013;Wolf Williams & Allen, 2015) while using a qualitative approach (Wolf Williams & Allen, 2015). Studies on this topic have focused on Black females (Arnold et al, 2018;Chance, 2021), while other studies included male and female leaders from diverse backgrounds and fields (i.e., African American, Haitian, Hispanic, White, German, Rwandan, British, Indigenous Guatemala) (Breisch & Lexmond, 2013;Wolf Williams & Allen, 2015). This study is also unique due to the researcher's positionality and identity as a Latina with a history of trauma.…”
Section: Significance Of the Studymentioning
confidence: 99%
See 1 more Smart Citation